Cell Stratification, Spheroid Formation and Bioscaffolds Used to Grow Cells in Three Dimensional Cultures - Hrebíková, Hana; Čížková, Dana; Chvátalová, Jana; Pisal, Rishikaysh; Adamčik, Richard; Beznoska, Pavel; Díaz-Garcia, Daniel; Mokrý, Jaroslav (Acta medica (Hradec Kralove), 2015)
The cell culture became an invaluable tool for studying cell behaviour, development, function, gene expression, toxicity of compounds and efficacy of novel drugs. Although most results were obtained from cell cultivation in two-dimensional (2D) systems, in which cells are grown in a monolayer, three-dimensional (3D) cultures are more promising as they correspond closely to the native arrangement of cells in living tissues. In our study, we focused on three types of 3D in vitro systems used for cultivation of one cell type. Cell morphology, their spatial distribution inside of resulting multicellular structures and changes in time were analysed with histological examination of samples harvested at different time periods. In multilayered cultures of WRL 68 hepatocytes grown on semipermeable membranes and non-passaged neurospheres generated by proliferation of neural progenitor cells, the cells were tightly apposed, showed features of cell differentiation but also cell death that was observable in short-term cultures. Biogenic scaffolds composed of extracellular matrix of the murine tibial anterior muscle were colonized with C2C12 myoblasts in vitro. The recellularized scaffolds did not reach high cell densities comparable with the former systems but supported well cell anchorage and migration without any signs of cell regression.
Keywords: hepatocyty; Animals; proliferace buněk; tkáňové podpůrné struktury; buněčné linie; Neurosphere; WRL 68 cells; lidé; tkáňové inženýrství; Mice; myši; Hepatocytes; Cell Line; myoblasty; 3D cell culture; Spheroids, Cellular; Cell Proliferation; Bioscaffold; Tissue Engineering; buněčné kultury; zvířata; Cell Culture Techniques; Myoblasts; Tissue Scaffolds; buněčné sféroidy; C2C12 cells; Humans